Innate Immune Function and Organ Failure Recovery in Adults With Sepsis. (June 2019) - Maddux, Aline B.; Hiller, Terra D.; Overdier, Katherine H.; Pyle, Laura L.; Douglas, Ivor S.
Purpose: Sepsis stimulates pro- and anti-inflammatory immune responses. The innate immune response is critical to organ injury repair. We tested for an association between innate immune function and organ function recovery in a prospective cohort of immune-competent adults with sepsis. Methods: We conducted a prospective observational cohort study enrolling immune-competent adults with sepsis. We tested innate immune function by quantification of lipopolysaccharide (LPS)-stimulated tumor necrosis factor (TNF) α production capacity in whole blood samples on hospital days 1, 4, and 6. The primary outcome was organ function recovery on day 4 defined as a 4-point decrease in the composite cardiovascular and respiratory Sequential Organ Failure Assessment (SOFA) score components or a SOFA score ≤2. Results: Patients with sepsis who recovered organ function by day 4 (n = 11) had similar baseline characteristics when compared to those with ongoing organ failure (n = 13). Tumor necrosis factor α production capacity was similar between the 2 groups on hospital days 1 and 4 but significantly different on day 6. Patients who regained organ function recovery had significantly higher TNF-α production capacity on day 6 ( P = .01), which persisted after adjustment for age, Acute Physiology and Chronic Health Evaluation III score, and steroid administration ( P = .03). There was no difference in TNF-α production capacity over time in those who survived to hospital discharge versus nonsurvivors. Conclusion: Increasing TNF-α production capacity is associated with improved organ failure recovery. Further studies are needed to evaluate a causal association between innate immune suppression and organ failure recovery as well as predictive accuracy for hospital survival. Impaired TNF-α production as a marker of sepsis-associated innate immune dysfunction may be a feasible target for immune stimulation to decrease time to organ failure recovery.